KAJIAN HUKUM DAN IMPLEMENTASI WAKAF HARTA BERGERAK DI INDONESIA: WAKAF UANG DAN SAHAM - Girindra Mega Paksi (Islam Institut Agama Islam Negeri Sultan Maulana Hasanuddin, 2018)
Abstract. The Implementation and Legality Review of Movable Treasure Endowments in Indonesia: Endowments of Money and Shares. Endowment or Waqf is a non-market wealth distribution methods alongside zakah, infaq, and sadaqa. Particularly in Indonesia, waqf practice is identical with fixed asset donation notably land and building. The utilization of most waqf asset in Indonesia is not economically productive, such as mosque and cemetery. The aims of this study are to analyze the precept of cash and share waqf and its implementations. This study is classified as a literature review with qualitative approach. A Meta-synthesis method is applied as analyzing tools. Results shows that most Islamic scholar allow cash and shares to be used as waqf object. Both cash and share waqf can be implemented into two models. Cash waqf can be implemented as mutual fund or converted into other fixed asset. While share waqf implementation can be done through corporate waqf and individual share waqf.